Managerial economics : principles and worldwide applications - Salvatore, Dominick; Rastogi, Siddhartha K. (New Delhi : Oxford University Press, 2016)
Reflecting the highly globalized nature of tastes, production, labour markets, and financial markets in today's world, this book presents the theory of the firm as a unifying theme to examine the managerial decision-making process. Adopting a global perspective, it synthesizes economic theory, decision science, and business administration studies, examining how they interact as a firm strives to reach optimal profitability and efficiency in the face of modern constraints.
Includes appendix and glossary.
Includes bibliographical references and index.
Economics
Keywords: Managerial economics; Managerial economics -- Textbooks